If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 36 = 48 Reorder the terms: 36 + 6x = 48 Solving 36 + 6x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 6x = 48 + -36 Combine like terms: 36 + -36 = 0 0 + 6x = 48 + -36 6x = 48 + -36 Combine like terms: 48 + -36 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 4t+.2=1.3 | | 2/3+2/3=n | | 6x+8=3x-20 | | 6x-8=3x-20 | | -2(y+7)=-4-16 | | 6x+1=7-6x | | 75x+15=25x | | 2x-5+4x+15+y=180 | | 3a+4+2a=2(5a-3) | | 6x+10+y=180 | | 1(-4)= | | 150(t)=16.1t^2+150 | | y=10x+11 | | 6(x+2)=26 | | 0=r^2-37.21 | | (-6)= | | 25.12=1/3(12.56h) | | 4z+9=0 | | 8(1-5v)-2=-274 | | 90=-6(3-3n) | | 6(2n+3)= | | 8(-8x-3)=232 | | 15=2x^2+5x-3 | | 4x+5y=103 | | 6+6(1+7a)=306 | | lxI+3=8 | | 0=-10x^2+3x+27 | | 4(x+10)(x-5)=0 | | -2y+4(8y-7)=4+9(-9-y) | | y=-0.05x^2+0.7x | | 14x-225=5x-9 | | (x-9)(y-2)=0 |